Genetic Polymorphism of β-Casein Gene in Polish Red Cattle—Preliminary Study of A1 and A2 Frequency in Genetic Conservation Herd - Cieślińska, Anna (Animals (Basel), 2019)
SIMPLE SUMMARY: Currently, milk and dairy products are considered nutritious foods because they contain bioactive constituents. However, in some cases, milk consumption might cause health-related issues, such as allergic reactions. Among all of the proteins present in milk, caseins deserve special attention. A genetic variant called β-casein is recognized as a potential cause of some health implications. However, although milk protein characteristics have been widely covered, a significant majority of published research focus on one cattle breed: Holstein There are numerous local breeds that have not been widely analyzed to date. One such breed is a dual-purpose breed called Polish Red. ABSTRACT: Although there is growing interest in Red cow’s milk in Poland, to date there are few reports investigating the characteristics of milk components in the studied population. Particular emphasis on milk proteins is advised, since β-casein is a source of bioactive peptides named β-casomorphins. β-casomorphin 7, which originates mostly from β-casein variants A1, may be a significant risk factor in human ischemic heart disease, arteriosclerosis, type I diabetes, sudden infant death syndrome, and autism. The aim of the present study was to identify CSN2 polymorphism gene in exon 7 using the genomic sequence from GenBank (M55158), g.8101C>A, (codon 67). Blood samples were collected from 201 Polish Red cattle (24 males and 177 females). The genotype of β-casein was determined using PCR-ACRS. The frequency of β-casein A2 in Polish Red population was 0.47. β-casein A2 frequency in Polish Red bulls and in cows was 0.58 and 0.37, respectively.